Pixel based Semantic Labelling and Image Parsing using Intelligent Learning Techniques - Srivastava, Vishal (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Pixel based Semantic; Labelling and Image Parsing using; Intelligent Learning Techniques